Sejarah Peran Teknologi dalam Perkembangan Ekonomi Syariah: Inovasi, Implementasi, dan Implikasinya - Yoyok Yuli Rianto, Slamet; Juni Alma, Windi; Maradona, Doni; Khirzan Nazar Noe`man, Muhammad; Puspita Sari Sudradjat, Winda (Journal of Comprehensive Science, 2025)
Sharia economics, which is based on the principles of Islamic law, has undergone significant transformations along with technological advancements. In recent decades, the development of digitalization, including blockchain technology and artificial intelligence (AI), has transformed the Islamic economic sector, especially in terms of transparency, security, and transaction efficiency. This technology supports the expansion of Islamic financial inclusion and accelerates the adoption of sharia-based financial services, such as Islamic digital banking. However, the main challenge faced is how to integrate sharia principles with rapidly developing technology. This research aims to analyze innovation, implementation, and the impact of technology in the sharia economy, as well as evaluate the challenges faced in its implementation. Using a qualitative approach and documentation studies, this study explores various technological innovations applied in the sharia economic sector and their impact on financial inclusion, community empowerment, and compliance with sharia principles.